Graphic Design Education: A Revised Assessment Approach to Encourage Deep Learning - Ellmers, G.; Foley, M.; Bennett, S. (Journal of University Teaching and Learning Practice, 2008)
In this paper we outline the review and iterative refinement of assessment procedures in a final year graphic design subject at the University of Wollongong. Our aim is to represent the main issues in assessing graphic design work, and informed by the literature, particularly 'notions of creativity' (Cowdroy & de Graaff, 2005), to develop and incorporate assessment procedures that allow creative ability to be assessed with greater transparency and objectivity. In the first iteration we developed a structure to standardise and clarify the existing model for the subject. Once this structure was in place we identified issues that would benefit from a review of the literature on assessment in the creative disciplines and the broader field of pedagogy.We marked the shift from surface approaches to learning to deep approaches to learning (Moon, 1999) at the point where we identified gaps in the learning outcomes. Our response was to move the focus from the outcome to the process and to introduce a staged assessment procedure with a stronger emphasis on formalised reflection, cycling throughout the design process. We divided the learning process into two streams: thinking and making as a means to clarify facets of learning.As we continue to refine this model we note and respond to the relationship between assessment and learning. We propose ideas for future investigation, based on identifying levels of design thinking achieved by students in the most recent iteration of the program, and how these might be improved.